Monochromatic image reconstruction by dual energy imaging allows half iodine load computed tomography coronary angiography - Carrascosa, Patricia (2015)
Purpose: To compare image interpretability and diagnostic performance of dual-energy CT coronary angiography (DE-CTCA) performed with 50% iodine load reduction versus single energy acquisitions (SE-CTCA) with full iodine load. Materials and methods: The present prospective study involved patients with suspected coronary artery disease (CAD) clinically referred for CTCA. DE-CTCA with 50% iodine volume load was performed first, and after heart rate returned to baseline SE-CTCA was performed using full iodine volume load. The primary endpoint was to compare image interpretability between groups. DE-CTCA was performed by rapid switching between low and high tube potentials (80–140 kV) from a single source, allowing the generation of monochromatic image reconstructions ranging from 40 to 140 keV. Image quality assessment was performed using a 5-point Likert scale. Results: Thirty-six patients constituted the study population. The mean heart rate before the CT scan (DE-CTCA 57.3 ± 10.7 bpm vs. SE-CTCA 58.5 ± 11.2 bpm, p = 0.29) and the mean effective radiation dose (3.5 ± 1.9 mSv vs. 3.8 ± 0.9 mSv, p = 0.48) did not differ between groups. Likert image quality scores were similar between groups (DE-CTCA 4.42 ± 0.98 vs. SE-CTCA 4.43 ± 0.84, p = 0.67). Signal-to-noise and contrast-to-noise ratios were significantly lower with DE-CTCA, driven by lower signal density levels at 60 keV compared to SE-CTCA. The sensitivity and specificity for the detection of stenosis >50% was indistinguishable between groups (DE-CTCA 84.4% (69.9–93.0%), 87.1% (81.6–91.2%); SE-CTCA 84.4% (69.9–93.0%), 87.1% (81.6–91.2%). Conclusions: In this pilot, prospective study, dual energy CTCA imaging with half iodine load achieved comparable interpretability than full iodine load with single energy CTCA.